Optimized Brain MRI Protocol for Epilepsy Diagnosis in Semarang, Indonesia: A Prospective Study - Istiqomah, Sarah Wilmar (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Epilepsy is a prevalent neurological disorder, and accurate diagnosis is crucial for effective management. Brain MRI plays a pivotal role in identifying epileptogenic foci. This study aimed to develop and evaluate an optimized brain MRI protocol for epilepsy diagnosis in Semarang, Indonesia, where access to advanced imaging may be limited. Methods: A prospective study was conducted at a tertiary care hospital in Semarang. Consecutive patients with suspected epilepsy underwent brain MRI using a standardized protocol comprising T1-weighted, T2-weighted, fluid-attenuated inversion recovery (FLAIR), and susceptibility-weighted imaging (SWI) sequences. Additional sequences like diffusion-weighted imaging (DWI) and post-contrast T1-weighted imaging were acquired when clinically indicated. Two experienced neuroradiologists independently reviewed the images, and their findings were correlated with clinical and electroencephalography (EEG) data. The diagnostic accuracy, sensitivity, specificity, and inter-rater agreement of the optimized protocol were evaluated. Results: A total of 150 patients (mean age 32.5 years, range 18-65 years) were enrolled. The optimized protocol identified epileptogenic lesions in 75 patients (50%), with the most common being mesial temporal sclerosis (30%), followed by focal cortical dysplasia (15%), and tumors (5%). The protocol demonstrated a sensitivity of 85%, a specificity of 92%, and an inter-rater agreement of 0.85 (kappa). The addition of DWI and post-contrast imaging improved the detection of subtle lesions and differentiation between tumor and inflammation. Conclusion: The optimized brain MRI protocol proved to be a valuable tool for epilepsy diagnosis in Semarang, with high diagnostic accuracy and inter-rater agreement. This protocol can be implemented in resource-constrained settings to improve the detection and characterization of epileptogenic lesions, leading to better patient management and outcomes.